All Questions Topic List
None Questions
Previous in All Question Next in All Question
Previous in None Next in None
Question Number 176540 by yaslm last updated on 20/Sep/22
Answered by Peace last updated on 21/Sep/22
F(x)=∫dxcos2(x)cos(x)=tg(x)1cos(x)−∫tg(x).sin(x)2cos(x)cos(x)−∫sin2(x)2cos2(x)cos(x)dx32F(x)=sin(x)cos(x)cos(x)+12∫dxcos(x)∫dxcos(x)=∫dx2cos2(x2)−1=∫dx1−2sin2(x2)=∫2dy1−2sin2(y)=2F(y∣2)=2F(x2∣2)F(x∣a2)=∫0xds1−a2sin2(s)ElepticintegralF(x)=23(tg(x)sec(x)+F(x2∣2))+c
Commented by Tawa11 last updated on 22/Sep/22
Greatsir
Commented by Peace last updated on 23/Sep/22
withePleasur
Terms of Service
Privacy Policy
Contact: info@tinkutara.com